Facile synthesis of pyrroloindoles via a rhodium(ii)-catalyzed annulation of 3-benzylidene-indolin-2-ones and α-imino carbenes. Issue 13 (25th January 2018) - Ma, Xueji; Xie, Xuemei; Liu, Li; Xia, Ran; Li, Tongyu; Wang, Hangxiang
Abstract : A novel carbenoid strategy to construct pyrrole-fused indole alkaloids. Abstract : The annulation of 3-benzylidene-indolin-2-ones with α-imino rhodium carbenes generated in situ from N -sulfonyl-1, 2, 3-triazoles is presented. Through the appropriate choice of catalyst, the reactions can be reasonably modulated, and consequently, a number of pyrroloindole derivatives were constructed in moderate to excellent yields.